Analysis of Acceptance of Digital Population Identity Applications Using The UTAUT Model - Nissa Adwitiya Aji; Asif Faroqi; Tri Lathif Mardi Suryanto (bit-Tech, 2025)
Digital transformation requires public services to operate more efficiently, transparently, and inclusively. In Indonesia, this shift is embodied in the Digital Population Identity (IKD) system, developed to modernize demographic administration and provide citizens with easier access to identity services. Despite achieving millions of downloads, IKD adoption still encounters notable challenges, including technical issues, complex interfaces, limited internet access in rural areas, and low levels of digital literacy. This study explores the factors influencing IKD adoption through the Unified Theory of Acceptance and Use of Technology (UTAUT). Using a quantitative design, data were collected from 408 valid respondents through purposive sampling and analyzed with Structural Equation Modeling–Partial Least Squares (SEM-PLS). The findings reveal that performance expectancy, effort expectancy, and social influence significantly affect user behavior, while facilitating conditions show no significant impact. The results emphasize that social support and perceived usability are stronger drivers of digital identity adoption compared to technical support, highlighting the importance of addressing user experience and societal influence. The study contributes theoretically by extending UTAUT in an e-government context, methodologically through SEM-PLS application, and practically by offering recommendations for improving system design, strengthening digital literacy initiatives, and ensuring IKD reliability. Future research is encouraged to incorporate additional constructs, such as habit or hedonic motivation, and to investigate adoption patterns across diverse regional settings.